Growth Toxic Effects of Metal Nanoparticles on Bacillus subtilis and Vibrio parahaemolyticus - Shiyu CHEN; Bin XIA; Lin ZHU; Shuang LI; Qiufen LI; Xuemei SUN; Wei DAI (Progress in Fishery Sciences)
Metal nanoparticles have been widely used in ceramics, the chemical industry, communication, and biomedicine because of their large specific surface area, small size, good photoelectric performance, and other excellent physical and chemical properties. With this widespread use, waste is inevitably produced that enters into the environment. Concurrently, organic colloids from natural sources, dust aerosols from volcanic eruptions, and other metal nanoparticles also widely exist in nature which can be transferred directly or indirectly into the ocean through sewage dumping, air subsidence, and surface runoff, thereby threatening marine environments. Marine bacteria are the most abundant microbial group in marine ecosystems and play an important role in matter circulation, energy flow, and the maintenance of marine ecosystem diversity. With the increase in the concentration of metal nanoparticles in the marine environment, their impact on the physiological ecology of marine bacteria needs further research. Recently, a new type of automated phenotypic method—the non-contact conductivity sensor (CCS) method—has been developed and applied to obtain data on the toxic effects of nanomaterials on bacteria. The improved capacitance-coupled noncontact conductivity detector is mainly used for online and real-time monitoring of the conductivity of microbial culture fluids. The obtained response values are proportional to the concentration and mobility of the ionic current in culture mediums. Since the uncharged or weakly charged substrate will be converted into highly charged small-molecule substances during the growth and proliferation of bacteria—thus increasing the culture medium conductivity—the bacterial growth process can be recorded quickly and accurately by detecting the change in the conductivity of the culture medium. Bacteria are divided into Gram-positive and Gram-negative according to their different cell structures. The cell wall of Gram-negative bacteria has a larger outer membrane composed of tightly packed lipopolysaccharide molecules than that of Gram-positive bacteria, which leads to different resistance effects to external stress. Bacillus subtilis and Vibrio parahaemolyticus—Gram-positive and Gram-negative bacteria, respectively—are widely present in marine environments and represent two important microbial categories. Among these, B. subtilis is a typical probiotic in the marine environment that plays a key role in promoting host health and environmental restoration. V. parahaemolyticus is a representative pathogenic bacterium in marine environments that can have notable impacts on foodborne diseases. Based on the ecological roles and functions of these two bacteria in marine microbial communities, this study used B. subtilis and V. parahaemolyticus isolated from Bohai Bay as test organisms. Common metal nanoparticles were used as research objects, and the CCS method was used to study their growth inhibitory effects on B. subtilis and V. parahaemolyticus. The research process included preparation of the bacterial solution where V. parahaemolyticus was inoculated in TCBS liquid medium at 28 ℃ for 12 h. The bacteria solution was dipped and streaked on the TCBS plate and cultured overnight. The single colonies on the plate were selected and inoculated into the new TCBS liquid medium at 28 ℃ for 12 h. The cultured bacterial solution was centrifuged, the supernatant was poured out, washed, and centrifuged twice with normal saline (0.85% NaCl), and the bacterial precipitate was re-suspended in normal saline for subsequent study. The preparation method for B. subtilis was the same as described above, and the medium used was LB. Additionally, the metal nanoparticle suspension was prepared. Finally, a growth toxicity test was done using B. subtilis and AgNPs as examples. Here, 10 mL of the prepared nano-gold (Ag NPs) suspension was measured in sterilized glass bottles. The prepared 100 μL B. subtilis solution was inoculated into this and mixed evenly. The 3 mL mixed system was absorbed with a sterile syringe and added into the NMR tube, with three tubes for each concentration and three tubes for each positive and negative control. For the positive control 10 mL medium and 100 μL bacterial solution were added into the NMR tube, and for the negative control, the same amount of medium was added into the NMR tube which was then put into the CCS instrument for measurement. The voltage at the excitation electrode of the instrument was 16 V and the frequency was 2 MHz. The instrument was set to collect data every 1 minute, and the experiment lasted for 12 h. The results showed that Au NPs, nano-silver (Ag NPs), nano-silver oxide (Ag2O NPs), and nano-titanium dioxide (TiO2 NPs) could inhibit the growth of B. subtilis and V. parahaemolyticus. The 12 h-EC20 values of Au NPS, Ag NPs, Ag2O NPS, and TiO2 NPs against B. subtilis were 1.81, 0.03, 1.71, and 54.43 mg/L, respectively, and those of V. parahaemolyticus were 8.11, 0.16, 2.97, and 81.55 mg/L, respectively. In the concentration range used here, nano-zinc oxide (ZnO NPs) and nano-iron oxide (Fe2O3 NPs) promoted the growth of V. parahemolyticus but showed an inhibitory effect on B. subtilis. The EC20 values obtained in this study can provide a theoretical basis for environmental risk assessment of the construction of metal nanomaterials in marine ecosystems in China.